Cover Feature: Modification of Ti‐doped Hematite Photoanode with Quasi‐molecular Cocatalyst: A Comparison of Improvement Mechanism Between Non‐noble and Noble Metals (ChemSusChem 10/2021). Issue 10 (28th April 2021) - Wang, Ruiling; Kuwahara, Yasutaka; Mori, Kohsuke; Qian, Xufang; Zhao, Yixin; Yamashita, Hiromi
Abstract : The Cover Feature shows a comparison of Ti‐Fe2 O3 photoanodes modified with quasi‐Fe(salen) and Ru(salen) as cocatalysts, which enhance the photocurrent density of Ti‐Fe2 O3 photoanode by 1.5 and 1.7 times, respectively. As a cocatalyst, the quasi‐Fe(salen) clearly increases the conductivity and reaction kinetics at the liquid–semiconductor interface, while the quasi‐Ru(salen) offers more metal sites to the electrolyte, which act as the new reaction sites. Both quasi‐Fe(salen) and Ru(salen) are effective as cocatalysts for photoelectrochemical water oxidation reaction with different advantages. More information can be found in the Full Paper by R. Wang et al .